1990
DOI: 10.1002/jcu.1990.18.9.685
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intrauterine Fetal Growth Retardation with Abdominal Circumference and Estimated Fetal Weight Using Cross‐Sectional Growth Curves

Abstract: The usefulness of a cross-sectional growth curve method in the detection of intrauterine growth retardation by ultrasonography was evaluated for abdominal circumference and estimated fetal weight. The patient sample consisted of 771 women with singleton pregnancy who delivered within seven days of an ultrasound scan. One hundred fifty-one (19.6%) women had infants with birth weight below the lOth percentile for menstrual age. Of these infants, 72.2% were symmetrically growth retarded on the basis of their neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…IUGR: fetus with an estimated fetal weight < 10th percentile by ultrasound [17] and growth arrest or pathologic PI of uterine arteries.…”
Section: Methodsmentioning
confidence: 99%
“…IUGR: fetus with an estimated fetal weight < 10th percentile by ultrasound [17] and growth arrest or pathologic PI of uterine arteries.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15] Other studies have evaluated the association of IUGR diagnosed on the basis of sonography and LBW but not other adverse neonatal outcomes. [16][17][18] However, most of these reports were case-control studies, making it difficult to evaluate the predictive value of sonography. One study identified an association between sonographic EFW in the first trimester of pregnancy and birth weight, birth weight for GA, and prematurity.…”
mentioning
confidence: 99%
“…Chinn (1992) made the same assumptions when analysing height for age, although she used a shifted log-transformation. In fetal medicine, it appears to be common (see for example Simon et al (1990) and Todros et al (1987)) to logtransform the response variable (e.g. birth weight) and to ®t a model of the form 0 1 T 2 T 3 where T is menstrual or gestational age.…”
Section: Logarithmic Transformationmentioning
confidence: 99%